Use of proton elastic scattering techniques to determine carbonaceous fractions in atmospheric aerosols collected on Teflon filters. (November 2015) - Chiari, Massimo; Calzolai, Giulia; Giannoni, Martina; Lucarelli, Franco; Nava, Silvia; Becagli, Silvia
Abstract: Amongst Ion Beam Analysis (IBA) techniques applied to the study of atmospheric aerosol samples, Elastic Backscattering Spectrometry (EBS) and Particle Elastic Scattering Analysis (PESA) with MeV energy proton beams allows obtaining quantitative information about the concentration of C and other low-Z atoms like H, N and O in the sample. With these nuclear techniques a direct measurement of elemental carbon (EC) and organic carbon (EC) is not possible. Nevertheless, the detection of all the aforemetioned light elements may help to infer some information on the aerosol chemical composition. The H concentration obtained by PESA may be used as a proxy of OC; then, EC can be obtained as the difference between total carbon measured simultaneously by EBS and OC as estimated by PESA. The feasibility of the quantification of EC and OC following this approach in particulate matter samples collected on Teflon filters, where this information cannot be obtained by standard thermo-optical analyses, will be discussed. Moreover, thanks to the simultaneous measurements of H, C, N and O in the aerosol samples, the organic component of the aerosols (particulate organic matter, POM) can be directly calculated and thus the validity of the POM/OC conversion factors found in the literature can be tested. Graphical abstract: Highlights: EBS and PESA measurements of C, N, O and H in aerosols collected on Teflon filters. Good agreement between TC concentrations measured by EBS and by thermo-optical analysis. A proxy measurement of OC and EC in aerosols collected on Teflon filters is obtained. Direct calculation of the particulate organic matter (POM) and of POM/OC ratios. We found POM/OC ratios of 1.5 (winter) and 1.8 (summer) for urban background site.